PENGEMBANGAN INSTRUMEN PEMBELAJARAN DARING UNTUK MATERI HUKUM PADA MATA PELAJARAN PPKn DI MGMP KABUPATEN KARANGANYAR - Noventari, Widya; Permata, Rima Vien; Triyanto, Triyanto; Suryono, Hassan; Rejekiningsih, Triyana; Gunawati, Dewi; Ariana, Yudi (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2021)
Community service as one part of the pillars of Tri Dharma college is carried out as a tangible manifestation of the role of collage in meeting community criticisms. Legal and Citizenship Research Group, FKIP, UNS in collaboration with MGMP PPKn SMA & SMK, Karanganyar Regency carried out Community Service activities aimed at PPKn SMA & SMK teachers as an effort to increase understanding and improve the quality of Civics learning in the development of online learning instruments, especially on material law. This community service activity aims to: 1) improve the mastery and understanding of Civics teachers on legal material, 2) increase knowledge and ability in compiling online learning instruments, 3) improve the ability of teachers in developing learning media in the online learning process. While the benefits of this activity are the maintenance of the continuity of the Tri Dharma of Higher Education functions, namely the functions of education, research, and community service. The method used is in the form of training (workshop) by providing understanding and prioritizing increasing teacher knowledge regarding strengthening legal material in Civics subjects and online learning instruments. This activity showed very satisfactory results. The teachers have very high enthusiasm to take part in this training and the ability to make online learning instruments and the development of learning media has increased.